A pilot study of complementary and alternative medicine use in patients with fibromyalgia syndrome - Wall GC; Krypel LL; Miller MJ; Rees DM (Centro de Investigaciones y Publicaciones Farmaceuticas, 2007)
Fibromyalgia syndrome (FMS) is a complex disorder, with primary symptoms of sleep disturbances, pain, and fatigue. FMS is one of the most common reasons for patient visits to a rheumatologist. Previous studies have suggested that complementary and alternative medicine (CAM) use in patients with rheumatic diseases is common, but such data specific to FMS patients is limited. Objective: The following study sought to describe the prevalence of CAM use in a primary care practice of patients with FMS and assess whether these patients discuss CAM use with their physician, physician-extender, and/or pharmacist. Methods: A one-group cross-sectional survey design was implemented in a large, community-based, private physician practice of patients diagnosed with FMS. A self-administered questionnaire was distributed during clinic visits. It solicited information related to demographic characteristics; FMS-specific health background; whether CAM use had been discussed with a health care provider; and the "ever-use" of common types of CAM. Respondents returned the questionnaire via US mail in a postage-paid, self-addressed envelope. Results: A total of 115 surveys were distributed with 54 returned for analysis (47% completion rate). The sample was predominantly female, well educated and had a mean age of 55.6 years. All respondents were White. Most respondents (92.6%) reported using some type of CAM. Exercise (92.2%), chiropractic treatment (48.1%), lifestyle and diet (45.8%), relaxation therapy (44.9%), and dietary and herbal supplements (36.5%) were most commonly reported CAM therapies "ever-used" by respondents. Dietary and herbal supplements with the highest prevalence of "ever-use" were magnesium (19.2%), guaifenesin (11.5%), and methylsulfonylmethane (MSM) (9.6%). Respondents most commonly discussed CAM with the clinic rheumatologist and the primary care physician (53.7% and 38.9%, respectively). Only 14.8% of respondents discussed CAM with a pharmacist. However, a significantly higher proportion of respondents who "ever-used" dietary and herbal supplements discussed CAM with a pharmacist compared to those who never used dietary and herbal supplements [chi square=6.03, p=0.014]. Conclusion: This pilot study suggests that CAM use is common in patients diagnosed with FMS. Compared to other healthcare providers, respondents were least likely to discuss CAM with a pharmacist. However, respondents who used dietary and herbal supplements were more likely to discuss CAM with a pharmacist compared to those who did not, suggesting the potential influence of pharmacist intervention.